PEDAGOGICAL BASIS AND PROBLEMS OF PROTECTING STUDENTS FROM THE THREAT OF HARMFUL INFORMATION IN THE EDUCATIONAL PROCESS (Scientific journal of the Fergana State University, 2023)
In the article, the author analyzes the pedagogical and psychological characteristics, the factors of protecting students from the threat of harmful information in the educational process, the mechanisms of interaction between teachers and parents in the formation of information literacy of students. The article also examines the preventive and effective components of the system for protecting students from the threat of malicious information, the problem of forming a critical attitude to other people's information while protecting students from the threat of malicious information.